The Life Span of Large Historical Databases - Jan Kok (Historical Life Course Studies)
Large historical databases, although intended to last for a long time, can become obsolete for a variety of reasons. In this essay these reasons are explored and used for a 'health check' of the Historical Sample of the Netherlands (HSN). The HSN leaders are examined for their visionary qualities and their sense of ownership, and the database for its complementarity, versatility and consistency. The essay concludes that, despite challenges ahead, HSN is sound of mind and body.